2013
DOI: 10.3329/bjas.v42i2.18504
|View full text |Cite
|
Sign up to set email alerts
|

Metabolites in the milk of buffalo, Holstein cross, indigenous and Red Chittagong cattle of Bangladesh

Abstract: Low molecular weight chemical compounds or intermediate products of a metabolism or other cellular processes are called metabolites. The objective of the present study was to investigate the variations in the metabolite concentration in the milk from crossbred water Buffalo (B), Holstein cross (H), Indigenous cattle (I) and Red Chittagong Cattle (R) and the relationships among those metabolites. The concentration of citric acid, ? -keto glutaric acid (?-keto GA), orotic acid, pyruvic acid, succinic acid, lacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Heat treatment may have an impact on citric acid content in milk, however, detailed investigation on this aspect should be performed [ 42 ]. Islam et al [ 44 ] studied the concentration of organic acids in raw, pasteurized and UHT milk and they reported that concentrations of organic acids increased in the storage [ 44 ]. Formic acid in heated milk is recognized as advanced product of Maillard reaction and amount of formic acid in sterilized milk was 150 times greater than normally pasteurized milk [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Heat treatment may have an impact on citric acid content in milk, however, detailed investigation on this aspect should be performed [ 42 ]. Islam et al [ 44 ] studied the concentration of organic acids in raw, pasteurized and UHT milk and they reported that concentrations of organic acids increased in the storage [ 44 ]. Formic acid in heated milk is recognized as advanced product of Maillard reaction and amount of formic acid in sterilized milk was 150 times greater than normally pasteurized milk [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Animal-(genetics, stage of lactation, ruminal fermentations, and udder infections) and feed-(grain, dietary protein intake, seasonal, and regional effects) related factors may account for variations in OA in raw milk. [30][31][32] With these factors the raw milk keeping conditions and the technological process (the severity and method of heat-treatment and homogenization pressure and temperature) and subsequent the storage conditions affect the concentrations of OAs in UHT milk. [3,5,33] There is no available data in literature on the variations and concentrations of OAs in UHT milk samples.…”
Section: Basic Chemical Compositionmentioning
confidence: 99%
“…The mean value of succinic acid was slightly lower than that reported by Gadaga et al [36] for UHT milk, and was higher than those (265 and 104 mg/L) in raw milk and pasteurized milk. [32,33] Compared to citric acid, succinic acid showed a wide coefficient of variation (35 versus 23%) which could explain that succinic acid has been derived from the different sources such as the oxidation of fatty acids during heat-treatment [33] and the fermentation of cellulose by cellulolytic bacteria in ruminants. [37] As shown in Table 2, the mean values of lactic and formic acids were higher than the findings (588 and 402 mg/L, respectively) of Ruas-Madiedo et al [34] for cow milk pasteurized at 63°C for 30 min.…”
Section: Basic Chemical Compositionmentioning
confidence: 99%